Impacts of climate change on tropical agroforestry systems: A systematic review for identifying future research priorities - Watts, Martin; Hutton, Craig; Mata Guel, Erik O.; Suckall, Natalie; Peh, Kelvin S.-H. (Frontiers in Forests and Global Change, 2022)
Climate change is expected to adversely affect the crop yields and food security for many smallholder farmers in the tropics unless adaptive measures are implemented. Agroforestry ecosystem services, such as micro-climate buffering, have received growing attention from the academic and policy communities for alleviating the negative impacts of climate change on smallholders. These benefits imply that agroforestry could offer a suitable measure for adaptation to climate change. However, whether agroforestry systems themselves succumb to the adverse effects of climate change is often less studied in the agroforestry literature. Consequently, less is known about how climate change will impact agroforests. We conducted a systematic review, which included an evidence quality assessment, to examine the impacts of climate change on tropical agroforestry systems (TAFS). Based primarily on studies undertaking biophysical approaches, we found that climate change negatively impacts TAFS by reducing tree growth, intensifying tree-crop resource competition and reducing crop yields. However, the impacts on smallholder farmers are less clear due to limited evidence in the relevant literature. We found that the evidence supporting our findings is mostly 'robust', although 'least robust' strength evidence was also commonly found. We conclude that to improve understanding of how climate change could affect the performance of TAFS as a social ecological system, more interdisciplinary studies are required. Furthermore, to improve the quality of evidence in the research field, studies should explore using mountain elevation gradients for climate analogue analysis to perform the most robust study designs. We provide an interdisciplinary conceptual model, which considers the interactions and feedbacks between TAFS components noted from our review to predict the response of ecosystem services provisioning and farmers' wellbeing to climate change, to guide interdisciplinary studies using climate analogue analysis.